Short Communication: Presence of the vulnerable freshwater goby Sicyopus auxilimentus (Gobiidae, Sicydiinae) on Sangihe Island, Indonesia: Sicyopus auxilimentus from Sangihe Island - VERYL HASAN; FITRI SIL VALEN; R. ADHARYAN ISLAMY; Maheno Widodo; ADITYA MIRZAPAHLEVI SAPTADJAJA; IZZUL ISLAM (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Hasan V, Valen FS, Islamy RA, Widodo MS, Saptadjaja AM, Islam I. 2021. Short Communication: Presence of the vulnerable freshwater goby Sicyopus auxilimentus (Gobiidae, Sicydiinae) on Sangihe Island, Indonesia. Biodiversitas 22: 571-579. A single specimen of freshwater goby Sicyopus auxilimentus was photographed and collected using fish traps between 8 and 15 September 2019 in the Laine waterfall, Sangihe island district, North Sulawesi Province, Indonesia. S. auxilimentus is amphidromous that live in both freshwater and marine environments. This species is currently listed as Vulnerable (VU) within the IUCN Red List Status. The specimen was identified as male S. auxilimentus based on the coloration of the preserved specimen: background yellowish; scale edges brown; posterior flanks and caudal peduncle orange; first dorsal fin black, second dorsal fin dusky black; pectoral fin slightly brown; ventral fin slightly dusky; anal fin blackish; caudal fin dusky brown. Specific morphological features were as follows: the base of the first dorsal fin was not connected to the second dorsal fin base; distance between the base of first and second dorsal fin was generally less than half of eye diameter; ventral fin rays were fused to belly only between fifth rays; posterior margin of caudal fins rays was rounded; scales were all ctenoid; scales appeared on the caudal peduncle, and between anal and second dorsal fins; anterior to which, scales became widely spaced and did not imbricate. Meristic characters were as follows: first dorsal fin rays VI; second dorsal fin rays I+9; ventral fin rays I+5; pectoral-fin rays 14; anal-fin rays I+9; caudal-fin rays 13; scales in lateral series 13; scales in zigzag series 7; scales in transverse series backward 7; scales in transerves series forward 4. This finding is considered the first record in Sulawesi and the fifth from Indonesian waters after findings in Halmahera, Java, Bali and Lombok. This record enhances the understanding of the distribution of S. auxilimentus in Indonesian waters. Monitoring is needed to assess the possibility of Sangihe Island being a growth ground, spawning ground, and/or on the migration route of S. auxilimentus. In the Laine waterfall, Sangihe island, freshwater conditions were as follows: salinity 3.5 psu, temperature 23-25°C, and dissolved oxygen 7.7-9.2 mg/l, which were ideal habitat for S. auxilimentus. S. auxilimentus from Sangihe Island, had 0.000 genetic distance than from S. auxilimentus from Bali, while the next closest genetic distance was S. zosterophorus at genetic distance of 0.090. In addition to onsite conservation, domestication programs are needed to increase commercial availability without depending on natural catches.